Role of orexin A signaling in dietary palmitic acid-activated microglial cells. (8th October 2015) - Duffy, Cayla M.; Yuan, Ce; Wisdorf, Lauren E.; Billington, Charles J.; Kotz, Catherine M.; Nixon, Joshua P.; Butterick, Tammy A.
Highlights: Palmitic acid (PA) increases microglial orexin receptor 1 expression. PA increases microglial pro-inflammatory cytokine release. Orexin A reduces microglial pro-inflammatory cytokine release. Orexin A attenuates hypothalamic cell death induced by PA-activated microglia. Orexin A may function as an immunomodulatory regulator of microglia. Abstract: Excess dietary saturated fatty acids such as palmitic acid (PA) induce peripheral and hypothalamic inflammation. Hypothalamic inflammation, mediated in part by microglial activation, contributes to metabolic dysregulation. In rodents, high fat diet-induced microglial activation results in nuclear translocation of nuclear factor-kappa B (NFκB), and increased central pro-inflammatory cytokines tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6). The hypothalamic neuropeptide orexin A (OXA, hypocretin 1) is neuroprotective in brain. In cortex, OXA can also reduce inflammation and neurodegeneration through a microglial-mediated pathway. Whether hypothalamic orexin neuroprotection mechanisms depend upon microglia is unknown. To address this issue, we evaluated effects of OXA and PA on inflammatory response in immortalized murine microglial and hypothalamic neuronal cell lines. We demonstrate for the first time in microglial cells that exposure to PA increases gene expression of orexin-1 receptor but not orexin-2 receptor. Pro-inflammatory markers IL-6, TNF-α, and inducible nitric oxide synthase in microglial cells are increased following PA exposure, but are reduced by pretreatment with OXA. The anti-inflammatory marker arginase-1 is increased by OXA. Finally, we show hypothalamic neurons exposed to conditioned media from PA-challenged microglia have increased cell survival only when microglia were pretreated with OXA. These data support the concept that OXA may act as an immunomodulatory regulator of microglia, reducing pro-inflammatory cytokines and increasing anti-inflammatory factors to promote a favorable neuronal microenvironment.